Performance, Microbial Populations, and Jejunal Morphology of Broilers Supplemented with Nano-Encapsulated Graviola Leaf Extract - U. Maesaroh; N. D. Dono; Zuprizal (Tropical Animal Science Journal, 2022)
This research was conducted to investigate the effects of adding nano-encapsulated graviola (Annona muricata Linn.) leaf extract (NGLE) to drinking water on microbial populations, jejunal morphology, and growth performance of broilers. A total of 300 seven-day-old Lohmann male broilers were allocated into 6 treatments with 5 replications and 10 chicks in each replicate pen. All birds were given the same basal diet but given drinking water treated with: drinking water only as a negative control (T1), drinking water + 25 mg/L Tetracycline (T2), drinking water + 15 mL/L GLE (T3), drinking water + 30 mL/L GLE (T4), drinking water + 15 mL/L NGLE (T5), or drinking water + 30 mL/L NGLE (T6). Variables observed in the current study included: body weight gain (BWG), final body weight (FBW), feed conversion ratio (FCR), feed intake (FI), carcass percentage, jejunal lactic acid bacteria (LAB), jejunal coliform bacteria, villus height and width, crypt depth, and crypt depth ratio. All variable data were statistically analyzed using a completely randomized design with one-way arrangement. Results showed that the addition of NGLE in drinking water improved (p<0.05) jejunal morphology, jejunal LAB, and growth performance of broiler chickens. The height of jejunal villus and population of jejunal LAB increased (p<0.01) when NGLE up to a dose of 15 mL/L was added into the drinking water. Supplementing 15 mL/L NGLE reduced (p<0.01) feed conversion ratio and improved (p<0.01) final body weight and carcass production compared with the other treatments. It is concluded that supplementation of 15 mL/L NGLE might be useful as an alternative for antibiotics growth promoters in poultry.